Growth Changes Of Soft Tıssue Profıle In Skeletal Class I And Class Iı Female; A Longıtudınal Study - Meliha Rübendüz; Dilek Erdem (Turkish Journal of Orthodontics, 2002)

(untitled)
The aim of this study was to examine longitudinally soft tissue profile changes in skeletal Class I and Class II female at pubertal stage. The material consisted of lateral cephalometric and hand-wrist films of skeletal Class I (12) and skeletal Class II (10) female which taken at pre-peak, peak and post-peak stages. The changes of soft tissue thickness, angular measurements of soft tissue profile and horizontal measurements from soft tissue points to SN vertical line were compared between the two groups and developmental stages. The differences between developmental stages were evaluated by using paired ‘t' test in Class I and Class II groups separetely. The differences between the two groups were evaluated by students T test. Decrease of soft tissue convexity was found different between the two groups at post-peak stage. The reason of this condition is that soft tissue convexity decreased in Class II group more than Class I group. Thickness of lower lip sulcus increased in Class II group at post-peak stage and in Class I group at pre-peak stage. The changes of horizontal measurements from lower lip and lower lip sulcus points to SN Vertical Line were statistically different between two groups at post-peak stage. These measurements increased in Class II group while no changes were found in Class I group.